EDITOR-IN-CHIEF'S LETTER TO THE READERS OF THE SPRING ISSUE "BAIKAL MEDICAL JOURNAL" - Igor Vladimirovich Malov (Байкальский медицинский журнал)
Dear readers of the Baikal Medical Journal! The editorial board strives to ensure that publications on the pages of our journal will allow a wide range of doctors, graduate students, residents, students of medical universities, scientists in the field of medicine and biology to receive modern and reliable scientific information on a wide range of issues of pathological physiology, internal diseases, surgery and related areas of medical knowledge. The format of the journal allows publishing experimental and clinical observations, original research, new techniques, literature reviews and lectures.